2005
DOI: 10.1021/jp058041a
|View full text |Cite
|
Sign up to set email alerts
|

A Two Transition State Model for Radical−Molecule Reactions:  A Case Study of the Addition of OH to C2H4

Abstract: A two transition state model is applied to the study of the addition of hydroxyl radical to ethylene. This reaction serves as a prototypical example of a radical-molecule reaction with a negative activation energy in the high-pressure limit. The model incorporates variational treatments of both inner and outer transition states. The outer transition state is treated with a recently derived long-range transition state theory approach focusing on the longest-ranged term in the potential. High-level quantum chemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

41
322
0
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 233 publications
(367 citation statements)
references
References 94 publications
(153 reference statements)
41
322
0
4
Order By: Relevance
“…Recent VARIFLEX calculations of rate constants for OH addition to hydrocarbons containing carbon double bonds have revealed similar differences. Greenwald et al (34) observed for the OH + ethene addition reaction that decreasing the energy of the transition state analogous to TS 2 by 1.0 kcal·kmol −1 , which is within the expected accuracy of their ab initio calculations, results in good agreement with experimental data between 300 and 400°K. A similar approach was adopted by Zador et al (35) in their computational investigations of the OH + propene addition reaction.…”
supporting
confidence: 70%
“…Recent VARIFLEX calculations of rate constants for OH addition to hydrocarbons containing carbon double bonds have revealed similar differences. Greenwald et al (34) observed for the OH + ethene addition reaction that decreasing the energy of the transition state analogous to TS 2 by 1.0 kcal·kmol −1 , which is within the expected accuracy of their ab initio calculations, results in good agreement with experimental data between 300 and 400°K. A similar approach was adopted by Zador et al (35) in their computational investigations of the OH + propene addition reaction.…”
supporting
confidence: 70%
“…Recently, this treatment has been applied to the case of the hydroxyl radical addition to ethylene. 49 At high temperatures, the outer transition state becomes unimportant and the kinetic model can be accurately approximated by including only the flux through the inner transition state. At 300 K, the inner transition state serves as the dominant bottleneck such that an inclusion of both transition states only reduces the rate by 30%.…”
Section: Resultsmentioning
confidence: 99%
“…Initially at large intermolecular distances the OH and unsaturated molecule will form a weakly bound van der Waals complex, and only if rearrangement of this to form a chemically bound adduct occurs via a submerged barrier (barrier is below the 65 reagent asymptote) will the reaction be fast at very low temperatures. 2,3 In this paper we report rate coefficients at low temperature for reactions of OH with ethene, ethyne and propyne, all of which have been observed in ISC 4 and planetary 70 atmospheres 5 . The reactions proceed via addition of OH to the double or triple bond forming a stable adduct, which is either stabilised by collisions or dissociates back to the reagents, leading to a pressure dependent rate coefficient.…”
mentioning
confidence: 96%